Isolation and Identification of Uranium Tolerant Phosphate-Solubilizing Bacillus spp. and Their Synergistic Strategies to U(VI) Immobilization - Zhong, Juan; Hu, Xuewu; Liu, Xingyu; Cui, Xinglan; Lv, Ying; Tang, Chuiyun; Zhang, Mingjiang; Li, Hongxia; Qiu, Lang; Sun, Weimin (Frontiers in Microbiology, 2021)
The remediation of uranium (U) through phosphate-solubilizing bacteria (PSB) is an emerging technique as well as an interesting phenomenon for transforming mobile U into stable minerals in the environment. While studies are well needed for in-depth understanding of the mechanism of U(VI) immobilization by PSB. In this study, two PSB were isolated from an U tailing repository site. These bacterial strains (ZJ-1 and ZJ-3) were identified as Bacillus spp. by the sequence analysis of 16S rRNA genes. Incubation of PSB in liquid medium showed that the isolate ZJ-3 could solubilize more than 230 mg L−1 P from glycerol-3-phosphate and simultaneously removed over 70% of 50 mg L−1 U(VI) within 1 h. During this process, the rapid appearance of yellow precipitates was observed. The microscopic and spectroscopic analysis demonstrated that the precipitates were associated with U-phosphate compound in the form of saleeite-like substances. Besides, scanning electron microscopy coupled with energy dispersive X-ray (SEM-EDS) and Fourier transform infrared spectroscopy (FTIR) analysis of the precipitates confirmed that the extracellular polymeric substances (EPS) might also play a key role in U sequestration. Furthermore, SEM and FTIR analysis revealed that part of U(VI) was adsorbed on the bacterial surface through cellular phosphate, hydroxy, carboxyl, and amide groups. This study provides new insights into the synergistic strategies enhancing U immobilization rates by Bacillus spp. that uses glycerol-3-phosphate as the phosphorus source, process of which contributes to harmful pollutant biodegradation.